151 Manganese enhanced magnetic resonance imaging in type 1 and type 2 diabetes mellitus. (6th June 2022) - Joshi, Shruti; Singh, Trisha; Kershaw, Lucy E; Spath, Nick B; Dattani, Abhishek; Gulsin, Gaurav S; Semple, Scott I; Williams, Michelle; Gibb, Fraser; Forbes, Shareen; Reynolds, Rebecca M; McCann, Gerry; et al.
Abstract : Introduction: The pathophysiology of diabetic cardiomyopathy has yet to be established although pre-clinical studies suggest a role for altered myocardial calcium handling. Manganese-enhanced magnetic resonance imaging (MEMRI) is a novel non-invasive method of assessing in vivo myocardial calcium handling. The purpose of this study was to investigate whether myocardial calcium handling is impaired in patients with either type 1 or type 2 diabetes mellitus in the absence of underlying heart disease. Methods: In a prospective case-control study, patients with type 1 (n=19) or type 2 (n=10) diabetes mellitus and healthy volunteers (n=15) underwent MEMRI. Participants with prior coronary artery disease, cardiomyopathy or an abnormal electrocardiogram were excluded. Manganese dipyridoxyl diphosphate (0.1 mL/kg) was administered over 10 min and myocardial T1 mapping was performed prior to and every 2.5 min for 30 min after contrast infusion (Figure 1). Quantitative manganese uptake analysis was performed by measuring T1 relaxation times in a region of interest within the interventricular septum and compared to the left ventricular blood pool. The rate of myocardial manganese uptake was determined by Patlak modelling [1].Results:Participants with type 1 and type 2 diabetes mellitus were older (50±13 and 55±15.3 years) than the healthy volunteers (32±10 years). All participants had preserved left ventricular ejection fraction (type 1 diabetes mellitus, 67.7±6.1%; type 2 diabetes mellitus, 66.8±3.2%; healthy volunteers, 65±3.5%). Mean myocardial manganese uptake was reduced in participants with both type 1 (6.4±0.6 mL/100 g of tissue/min) and type 2 (6.4±0.5 mL/100 g of tissue/min) diabetes mellitus compared with healthy volunteers (8.3±0.5 mL/100 g of tissue/min; p<0.0001 for both, Figure 2). There were no differences in myocardial manganese uptake between those with type 1 or type 2 diabetes mellitus (p=0.22). There was no statistically significant correlation between myocardial manganese uptake and age in the study population (r=-0.28, p=0.07). Conclusion: Using MEMRI, we have demonstrated that myocardial calcium handling is impaired in patients with either type 1 or type 2 diabetes mellitus even in the absence of left ventricular systolic dysfunction. This suggests altered myocardial calcium handling may underlie, or contribute to, diabetic cardiomyopathy which has implications in developing novel therapeutic targets for the prevention and treatment of diabetic cardiomyopathy. [1] Skjold, A et al. J Magn Reson Imaging 2006;24:1047–1055. Conflict of Interest: None